Taxonomic revision of the Neotropical genus Telemiades Hübner, [1819 (Lepidoptera: Hesperiidae: Eudaminae), with descriptions of fourteen new species - Siewert, Ricardo Russo; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (Zootaxa, 2020)
Telemiades Hübner, [1819] is currently comprised of 22 species and 14 subspecies distributed exclusively in the neotropics. The genus is defined by the morphological pattern of the uncus, apiculus, labial palpi and venation. However, some species have a uniform pattern of coloration making it difficult to establish their correct identity in some cases. The aims of the present study were to present a taxonomic revision of Telemiades Hübner, [1819] in order to provide a stable taxonomic hypothesis for the group, to describe the new species and to present diagnoses to help in species identification. According to the present study, Telemiades is now composed of 41 species. Fourteen new species are recognized and described. Three subspecies are here treated as valid species: T. marpesus (Hewitson, 1876) stat. rest., T. misitheus Mabille, 1888 stat. rest. and T. pekahia (Hewitson, 1868) stat. rest. Two synonyms are treated as valid species: T. insulsus (Draudt, 1922), stat. rev. and T. xantho Hayward, 1939 stat. rev. Five new synonyms are proposed: Plesioneura lamus Mabille, 1888 syn. nov. and Telemiades antiope tosca Evans, 1953 syn. nov. of T. antiope (Plötz, 1882), Echelatus punctatus Mabille & Boullet, 1917 syn. nov. of T. epicalus Hübner, [1819], Proteides nicola Plötz, 1882 syn. nov. of T. laogonus (Hewitson, 1876) and Eudamus phlius Plötz, 1881 syn. nov. of T. nicomedes (Möschler, 1879). To provide stability for existing names, six neotypes were designated for: Proteides amphion Geyer, 1832, Plesioneura compressa Möschler, 1877, Papilio avitus Stoll, 1781, Telegonus mygdon Möschler, 1877, Proteides aesopus Plötz, 1882 and Papilio corbulo Stoll, 1781; and 19 lectotypes for: Aethilla buffumi Weeks, 1906, Eudamus marpesus Hewitson, 1876, Telemiades misitheus Mabille, 1888, Pterygospidea pekahia Hewitson, 1868, Telemiades lurideolus Mabille, 1877, Eudamus laogonus Hewitson, 1876, Eudamus penidas Hewitson, 1867, Telemiades ceramina Herrich–Schäffer, 1869, Telemiades megalloides Schaus, 1902, Pythonides hoyti Weeks, 1906, Eudamus praestes Hewitson, 1876, Telemiades epicalus Hübner, [1819], Eudamus phasias Hewitson, 1867, Telemiades arcturus Herrich–Schäffer, 1869, Echelatus punctatus Mabille & Boullet, 1917, Eudamus centrites Hewitson, 1870, Telegonus gallius Mabille, 1888, Telegonus nicomedes Möschler, 1879, and Arteurotia meris Plötz, 1886.